Parental Beliefs, Investments, and Child Development : Evidence from a Large-Scale Experiment - Carneiro, Pedro; Galasso, Emanuela; Lopez Garcia, Italo; Bedregal, Paula; Cordero, Miguel (World Bank, Washington, DC, 2019)
This paper experimentally evaluates a large-scale and low-cost parenting program targeting poor families in Chile. Households in 162 public health centers were randomly assigned to three groups: a control group, a second group that was offered eight weekly group parenting sessions, and a third group that was offered the same eight group sessions plus two sessions of guided interactions between parents and children focused on responsive play and dialogic reading. Three years after the end of the intervention, the receptive vocabulary and the socio-emotional development of children of families participating in either of the treatment arms improved (by 0.43 and 0.54 standard deviation, respectively) relative to children of nonparticipating families. There were no statistically detectable impacts on other types of skills. The treatments also led to improvements in home environments and parenting behaviors of comparable magnitudes, which far outlasted the short duration of the intervention. A simple mediation analysis suggests that up to 13 percent of treatment impacts on language, and up to 36 percent of impacts on child socio-emotional development, can be attributed to changes in the home environment, as well as in nurturing and discipline parenting behaviors.